2017
DOI: 10.1021/acs.jpcc.7b02733
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Tuning of the Surface Plasmon Resonance of Indium Tin Oxide Nanocrystals by Gas-Phase Oxidation and Reduction

Abstract: Heavily doped oxide nanocrystals exhibit a tunable localized surface plasmon resonance (LSPR) in the infrared, a property that is promising for applications in photonics, spectroscopy, and photochemistry. Nanocrystal carrier density and, thus, spectral response are adjustable via chemical reaction; however, the fundamental processes that govern this behavior are poorly understood. Here, we study the time dependence of the LSPR supported by indium tin oxide (ITO) nanocrystals during O2 and N2 annealing with in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…Solution NMR Spectroscopy. Solution 19 F NMR was performed using a 400 MHz Bruker AVIII spectrometer. The concentration of the NOBF 4 in MeCN solution was determined using a known concentration of 1,2,4,5-tetrafluorobenzene as an internal standard and by measuring the ratio of the integrated NOBF 4 feature to the tetrafluorobenzene signal, following the procedure in ref 58.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Solution NMR Spectroscopy. Solution 19 F NMR was performed using a 400 MHz Bruker AVIII spectrometer. The concentration of the NOBF 4 in MeCN solution was determined using a known concentration of 1,2,4,5-tetrafluorobenzene as an internal standard and by measuring the ratio of the integrated NOBF 4 feature to the tetrafluorobenzene signal, following the procedure in ref 58.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…While much of the PSNC research has focused on ITO, studies on Al:ZnO reveal plasmonic behavior that is size, dopant, and reaction dependent. ,, n -type ZnO is an industrially important material, as it has long been studied as a less expensive alternative to indium tin oxide (ITO) for transparent conducting oxide applications. M:ZnO nanocrystals (MZO NCs, where M = Al 3+ , Ga 3+ , or In 3+ ) exhibit a localized surface plasmon resonance (LSPR) in the MIR region. , Such low frequency LSPRs make these materials important for applications such as surface-enhanced Raman , and thermal waste management. , The method developed by Hutchison and co-workers for the controllable synthesis of metal oxide PSNCs was modified by Gaspera and co-workers for ZnO based systems, allowing for a broader study of the group III dopant effects on the LSPR in ZnOs …”
Section: Introductionmentioning
confidence: 99%
“…Change in refractive index of the medium was also considered; however, because refractive index is a reversible phenomenon and all of the optical property measurements were taken at room temperature, it was clear that it has no effect on the shifting spectral properties. Therefore, the main factors contributing to the spectral changes of ITO were the distribution of Sn 4+ throughout In 2 O 3 , reduction of interstitial oxygen, liberation of carriers from Sn–O traps, carrier mobility, and increased order of the In 2 O 3 host matrix. ,, ,, …”
Section: Resultsmentioning
confidence: 99%
“…In addition, no diffraction lines belonging to free Sn–O were observed in either the room-temperature or heated samples. Although the diffraction lines are relatively broad, making it hard to convincingly dispel the presence of tin oxide species, other researchers already reported that the presence of tin–oxygen complexes would result in decreased carrier concentration due to the carrier traps usually generated by such species. ,, However, the lack of appreciable amounts of tin–oxygen complexes can be inferred by the spectral blue shift and absorbance increase after heating. On the contrary, others have discovered that heating ITO thin films to temperatures exceeding 300 °C led to increased crystallinity. , As a result, diffraction lines increased with every 100 °C increment of the annealing temperature, indicating improved crystallinity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation